Costs of unsafety in aviation - Čokorilo, Olja; Gvozdenović, Slobodan; Vasov, Ljubiša; Mirosavljević, Petar (Technological and Economic Development of Economy, 2010)
The purpose of this paper is to define an analytical tool intended to provide a sound, technically justifiable, and consistent approach to analyzing the risk posed by aircraft accidents. The methodology presented in this paper takes into consideration items determined to be important to understanding the risk of aircraft accident and safety appraisal. These items include a number of aircraft operations/flights; crash probabilities; aircraft characteristics; costs, revenues, socio‐economic benefits, value statistical life, etc. The presented case study gives various cost assessments for an A320 crash depending on accident severity and aircraft age. It could be used as a risk assessment tool for implementing safety management system (SMS) process. Article in English. Išlaidos, patiriamos aviacijoje dėl nesaugumo Santrauka. Šio straipsnio tikslas ‐ aprašyti analizės priemonę, skirta patikimai ir techniškai pagrįstai orlaivių avarijų rizikos analizei. Straipsnyje pateikta metodika gali įvertinti svarbiausius orlaivių avarijų rizikos ir saugos aspektus: tai orlaivių skrydžių skaičius; avarijų tikimybė; orlaivio charakteristikos; išlaidos; pajamos; socialinė ir ekonominė nauda; statistinė eksploatavimo trukmė ir pan. Pavyzdyje pateikiamas įvairių orlaivio A320 avarijos sąnaudų vertinimas priklausomai nuo įvykio sunkumo ir orlaivio amžiaus. Vertinimo metodika galėtų būti taikoma kaip rizikos vertinimo priemonė, diegiant saugos valdymo sistema (SVS). Reikšminiai žodžiai: rizikos valdymas, saugumas, orlaivių avarijų išlaidos. First published online: 09 Jun 2011